(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article provides general information about the polymer reagent “FAR-PANC MCP” and studies some of its properties. Information is provided about some of its solvents, among which the optimal ones are selected.